2013
DOI: 10.1098/rspb.2013.0401
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of sexual dimorphism in New Zealand giant moa (Dinornis) and other ratites

Abstract: The extinct giant moa Dinornis is one of the most remarkable known examples of reversed sexual size dimorphism (RSD), with males weighing 34-85 kg, but females weighing up to 240 kg. However, there has been little consideration of the evolutionary mechanism that produced this level of dimorphism, and most living palaeognaths also exhibit varying levels of RSD. Using male and female body mass data for extant ratites and tinamous and four extinct moa genera, and tests of phylogenetic dependence (l) of body size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“… Graphical comparison of the published estimates of mean moa population density (all species combined) across New Zealand. The studies are as follows: (1, Caughley ); (2, Batcheler ); (3, Anderson ); (4, Holdaway and Jacomb ); (5, Gemmell et al 2004); (6, Forsyth et al ); (7, Lee et al ); (8, Tanentzap et al ); (9, Perry et al ); and (10, this study). For Perry et al () and this study, values shown are the 95% quantile range (bars) and mean (point).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“… Graphical comparison of the published estimates of mean moa population density (all species combined) across New Zealand. The studies are as follows: (1, Caughley ); (2, Batcheler ); (3, Anderson ); (4, Holdaway and Jacomb ); (5, Gemmell et al 2004); (6, Forsyth et al ); (7, Lee et al ); (8, Tanentzap et al ); (9, Perry et al ); and (10, this study). For Perry et al () and this study, values shown are the 95% quantile range (bars) and mean (point).…”
Section: Discussionmentioning
confidence: 95%
“…Where species are sympatric and have overlapping ecological niches, one species may be competitively dominant and depress population densities of subordinate species (Dayan and Simberloff ). Four or more species of moa occurred in sympatry at some South Island locations (Worthy 1990, Worthy and Holdaway , Wood et al , Fig. A).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An extreme reversed sexual size dimorphism was found in the Moa (Dinornithidae), extinct giant ratites endemic to New Zealand (Bunce et al 2003;Olson and Turvey 2013). In these New Zealand Moa, the largest females reached about 150 % the height and 280 % the weight of the largest males.…”
Section: Sexual Size Dimorphismmentioning
confidence: 97%